2022
DOI: 10.3389/fonc.2022.852347
|View full text |Cite
|
Sign up to set email alerts
|

Cause of Death Among Patients With Thyroid Cancer: A Population-Based Study

Abstract: BackgroundOver the last decades, the number of patients diagnosed with thyroid carcinoma has been increasing, highlighting the importance of comprehensively evaluating causes of death among these patients. This study aimed to comprehensively characterize the risk of death and causes of death in patients with thyroid carcinoma.MethodsA total of 183,641 patients diagnosed with an index thyroid tumor were identified from the Surveillance, Epidemiology, and End Result database (1975–2016). Standardized mortality r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…Recent years, several studies have suggested that cancer patients have a higher risk of CVD related death compared with general population (12,14). Wang's study showed that the cardiovascular mortality rates of 1, 3 and 5 years in cancer patients were 6.0%, 10.8% and 17.9%, respectively, and the total cardiovascular mortality rates were 25.8% (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent years, several studies have suggested that cancer patients have a higher risk of CVD related death compared with general population (12,14). Wang's study showed that the cardiovascular mortality rates of 1, 3 and 5 years in cancer patients were 6.0%, 10.8% and 17.9%, respectively, and the total cardiovascular mortality rates were 25.8% (17).…”
Section: Discussionmentioning
confidence: 99%
“…Our study have several limitations: first, factors such as patient's comorbidities (hyperlipidemia, diabetes, dyslipidemia, obesity and history of CVDs), bad habits (alcohol use and smoking habit), family history, detailed information of radiation and chemotherapy (type, dosage, and duration) may influence CVD related death in EC patients, but these information are not included in the SEER database (12,14). Second, because only…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvements in the detection of TC and therapeutic strategies have likewise resulted in a more favorable course for this disease. Because the mortality rates for TC remained stable at around 0.5 deaths per 100,000, the number of patients surviving is on the rise (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al reported that the non-cancer cause was the dominant cause of death (10,387 out of 22,386) in patients with thyroid cancer. The proportion of thyroid-caused death and other cancer-caused death were 31.0 and 22.6%, respectively ( 38 ). Based on 834,510 colorectal cancer patients, Chen et al concluded that the mortality risk from non-cancer cause increased.…”
Section: Discussionmentioning
confidence: 99%